2007
DOI: 10.1109/iembs.2007.4352595
|View full text |Cite
|
Sign up to set email alerts
|

On the reliability of pulse oximetry at the sternum

Abstract: Non-invasive assessment of arterial oxygen saturation has traditionally been entrusted to pulse oximetry. Whereas commercial probes are confined to the finger tip or the forehead, several recent works aim at enlarging the range of placement sites. In the context of the development of a continuous multi-parameter health monitoring system, CSEM is exploring the reliability of pulse oximetry measurements at the sternum. This talk will address both theoretical and practical aspects of the development of such a sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The concept of PPG and pulse oximetry at the sternum is has been demonstrated recently by [15]. Our findings showed that the parasympathetic and sympathetic autonomic modulation of the heart rate can be measured from PRV analysis using sternal PPG on a healthy group of subjects at rest.…”
Section: Discussionmentioning
confidence: 54%
“…The concept of PPG and pulse oximetry at the sternum is has been demonstrated recently by [15]. Our findings showed that the parasympathetic and sympathetic autonomic modulation of the heart rate can be measured from PRV analysis using sternal PPG on a healthy group of subjects at rest.…”
Section: Discussionmentioning
confidence: 54%
“…The vascular properties of the skin differ between various locations on the body. The tissue at the sternum is less perfused when compared with the peripheral locations such as the fingertip [8]. Nevertheless, acquiring the RR from sternal PPG has several advantages that make the sternum an appropriate sensor position.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by Nilsson et al [7] who found that the respiratory and cardiac induced variations in the PPG were different at different measuring sites (finger, forearm, wrist, forehead, and shoulder). The application of pulse oximetry using PPG at the sternum has recently been demonstrated [8]. However, the extraction of the RR from sternal PPG has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…We are targeting a location on truncus either ventral or dorsal and we are currently investigating this. Pulse oximetry on the sternum have previously been demonstrated by [16], but it needs more investigation before it can be used clinically.…”
Section: Pulse Oximetry Applicationmentioning
confidence: 99%